2006
DOI: 10.1262/jrd.18051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ski in the Granulosa Cells of Atretic Follicles in the Rat Ovary

Abstract: Abstract. The aim of the present study was to locate Ski protein, a product of cellular protooncogene c-ski, in rat ovaries in order to predict the possible involvement of Ski in follicular development and atresia. First, expression of c-ski mRNA in the ovaries of adult female rats was confirmed by RT-PCR. Then, ovaries obtained on the day of estrus were subjected to immunohistochemical analysis for Ski and proliferating cell nuclear antigen (PCNA) in combination with terminal deoxynucleotidyl transferase-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Members of the TGF-b superfamily are critical regulators of follicle development, especially GDF-9 and BMP-15, which are expressed in an oocyte-specific manner from a very early stage and play a key role in promoting follicle growth beyond the primary stage [5]. TGF-b superfamily members are not the only factors to be expressed by oocytes, granulosa cells, and theca cells in a developmental stage related manner, functioning as intraovarian regulatory molecules vital to follicle recruitment, granulosa and theca cell proliferation/atresia, steroidogenesis, oocyte maturation, ovulation, and luteinization [6,7]. TGF-b superfamily receptors, ligands, and binding proteins are also expressed in a developmental stage manner in different ovarian compartments [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the TGF-b superfamily are critical regulators of follicle development, especially GDF-9 and BMP-15, which are expressed in an oocyte-specific manner from a very early stage and play a key role in promoting follicle growth beyond the primary stage [5]. TGF-b superfamily members are not the only factors to be expressed by oocytes, granulosa cells, and theca cells in a developmental stage related manner, functioning as intraovarian regulatory molecules vital to follicle recruitment, granulosa and theca cell proliferation/atresia, steroidogenesis, oocyte maturation, ovulation, and luteinization [6,7]. TGF-b superfamily receptors, ligands, and binding proteins are also expressed in a developmental stage manner in different ovarian compartments [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the Ski protein is expressed in granulosa cells of atretic follicles [20]. In order to determine if the Ski-positive cells that appeared after hCG treatment were the cells that were undergoing apoptosis, we analyzed apoptosis of these cells using a TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analyses of Ski were performed as described previously [20]. In brief, frozen tissue sections (5 μm thick) prepared from the OCT-embedded rat ovary using a cryostat (Microm HM550, Carl Zeiss Japan, Tokyo, Japan) were mounted on glass slides, fixed in 4% paraformaldehyde (PFA) in phosphate bufferedsaline (PBS) for 20 min and then incubated in 0.1% Triton X-100 in PBS for 15 min.…”
Section: Immunohistochemistry and Tunel Stainingmentioning
confidence: 99%
See 2 more Smart Citations